“There's always something, and then there's more”: a qualitative examination of how virtual peer led self-management can create community around the evolving SCI experience - Starosta, Amy J.; Tyman, Shannon; Garbaccio, Chris; Chapman, Jayden; Hoffman, Jeanne M. (Frontiers in Rehabilitation Sciences, 2024)
Introduction: Self-management programs for spinal cord injury (SCI) are a growing adjunct to traditional healthcare services aiding individuals with SCI in learning and managing symptoms and medical care. Benefits of self-management programs are they can be facilitated by peers, offering unique lived experience of adjusting to and managing SCI. While a growing body of literature highlights the effectiveness of peer-led programs, there is limited understanding of how individuals engage with peer programs or critical components of peer support. Current study seeks to understand how individuals engaged with peers a self-management program. Methods: Secondary qualitative analysis of online forum posts resultant from a peer led self-management course for SCI. Results: Content analysis revealed several themes of how participants engaged with members of the group, including skill building, resource sharing, and problem solving. A process level theme of emotional connection to others living with similar SCI-related challenges was defined as "bearing witness." Participants commented that groups were the first time they engaged with community with lived experience, and shared experience was frequently highlighted in responses from individuals as one of the most unique and important aspects of the intervention. Discussion: Themes identified suggest bearing witness was a critical component of peer led intervention. While self-management content provided structure for engagement and discussion, participants report connectedness and shared experience made content more impactful and relevant. Future research should examine if alignment of peer and participant experience increases the impact of interventions and explore if this theme is important for other chronic medical populations.